2017
DOI: 10.4269/ajtmh.17-0589
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Paralytic Shellfish Poisoning in Sabah, Malaysia

Abstract: During the months of January-February and May-June 2013 coinciding with the red tide occurrence in Kota Kinabalu, Sabah, Malaysia, six episodes involving 58 cases of paralytic shellfish poisoning (PSP) or saxitoxin (STX) poisoning and resulting in four deaths were reported. Many of them were intoxicated from consuming shellfish purchased from the markets, whereas others were intoxicated from eating shellfish collected from the beach. Levels of STX in shellfish collected from the affected areas were high (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…A total of 11 articles were finally considered and included in this review. Overall, the most recent articles were published in 2017 [13][14][15][16][17], and the oldest article was published in 2010 [18]. All of the included articles were descriptive studies.…”
Section: General Characteristics Of the Included Articles For The Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 11 articles were finally considered and included in this review. Overall, the most recent articles were published in 2017 [13][14][15][16][17], and the oldest article was published in 2010 [18]. All of the included articles were descriptive studies.…”
Section: General Characteristics Of the Included Articles For The Reviewmentioning
confidence: 99%
“…Five out of the 11 articles reported on malaria infection [13,[19][20][21][22], two of the articles reported on seafood poisoning [15,16], and two articles reported on tuberculosis (TB) disease [18,23]. A study assessed the antenatal care practice and pregnancy outcome [17], and another study measured iodine status among pregnant women [14].…”
Section: General Characteristics Of the Included Articles For The Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous fatal cases of PSTs have been reported globally [ 12 ]. Toxic blooms with PSTs in Basha in 2013 have resulted in the intoxication of 58 people with 4 fatalities (records from the Sabah Health Department, Malaysia) [ 13 ]. With continuous research on the algae–bacteria relationship, bacteria with algicidal activity have been shown to play an important role in controlling HABs by lysing algal cells [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saxitoxins, comprising 57 compounds, are a potent neurotoxin blocking ionic sodium and calcium channels, resulting in rapid paralysis and respiratory failure [ 7 ]. The passing of either MCs and/or STXs through the aquatic food web leads to animal deaths and human poisonings [ 8 , 9 ]. The World Health Organization (WHO) and the United States Environmental Protection Agency (EPA) have set guidelines to minimize MCs’ hazards [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%